Pengaruh Stabilitas Keuangan, Tekanan Eksternal Dan Rasionalisasi Terhadap Kecurangan Laporan Keuangan (Financial Statement Fraud) Pada Perusahaan Yang Bergerak Dibidang Konstruksi Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022 - Julianti, Desak Putu; Kusumawati, Ni Putu Ayu; Padnyawati, Kadek Dewi (UNHI Press, 2025)
Financial statement fraud refers to the intentional manipulation of accounting information, aiming to distort crucial details or present deceptive data, ultimately influencing the decisions and perceptions of stakeholders based on misrepresented facts. This investigation aims to analyze the potential triggers of financial statement fraud in construction sector firms listed on the Indonesian Stock Exchange between 2020 and 2022, examining the intersection of financial stability, external pressures, and rationalization. Employing a non-probability sampling method, specifically saturated sampling, 21 companies operating in the construction sector were selected, resulting in 63 observation data over a 3year period. Secondary data was utilized for analysis. The research findings suggest that while financial stability and external pressures do not significantly impact the occurrence of financial statement fraud, rationalization plays a crucial role in its manifestation.